Distribusi Spasial Fitoplankton di Perairan Pesisir Tangerang - Dwi Yuni Wulandari; Niken Tunjung Murti Pratiwi; Enan Mulyana Adiwilaga (Jurnal Ilmu Pertanian Indonesia, 2014)
This study was conducted in describing the spatial distribution of phytoplankton in the coast of Tanggerang based on species composition and abundance. This study held on April and August 2013 in 10 sampling station. Sample survey method used to collect the data. Morisita Index of Dispersion used to describe the distribution pattern of phytoplankton and Bray-Curtis Index used to describe the similarity of sampling station based on its abundances of phytoplankton. Based on result of the study, the phytoplankton in the coast of Tangerang consist of three classes, which is Bacillariophyceae (24 genera), Dinophyceae (3 genera), and Cyanophyceae (2 genera). The result shows that the highest composition and abundance is from the species of Bacillariophyceae. The distribution pattern of phytoplankton is group distribution. The distribution of species of phytoplankton and its abundance is different even the sampling station is near each other and environmental parameters that influence.